2020
DOI: 10.1186/s12893-020-00988-1
|View full text |Cite
|
Sign up to set email alerts
|

Dermatome Mapping Test in the analysis of anatomo-clinical correlations after inguinal hernia repair

Abstract: Background Nerve identification is recommended in inguinal hernia repair to reduce or avoid postoperative pain. The aim of this prospective observational study was to identify nerve prevalence and find a correlation between neuroanatomy and chronic neuropathic postoperative inguinal pain (CPIP) after 6 months. Material A total of 115 patients, who underwent inguinal hernia mesh repair (Lichtenstein tension-free mesh repair) between July 2018 and January 2019, were included in this prospective observational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The bias of this results is the lower number of studies included in these analyses (only half of the papers included reported data at 6 months and only one paper reported data at 12 months), as well as the heterogeneous evaluation of these data for the absence of a common standardized system. The improved use of Dermatome Mapping Test in common clinical practice can represent an adequate system for the standardization of future RCTs [66]. In the current torrent of data, cautions are needed for the lack of this additional crucial information about paresthesia and hypoesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bias of this results is the lower number of studies included in these analyses (only half of the papers included reported data at 6 months and only one paper reported data at 12 months), as well as the heterogeneous evaluation of these data for the absence of a common standardized system. The improved use of Dermatome Mapping Test in common clinical practice can represent an adequate system for the standardization of future RCTs [66]. In the current torrent of data, cautions are needed for the lack of this additional crucial information about paresthesia and hypoesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, we reported that the prophylactic IIN neurectomy seems to offer some advantages concerning postoperative inguinal pain in the first 6th month period, but this advantage is associated with the risk of hypoesthesia that it is higher in recent post‐operative analysis performed with Dermatome Mapping Test (14.8%) [4].…”
Section: Figurementioning
confidence: 99%
“…lifting and twisting of the cord. The difficult identification of GB is well-reported in the surgical literature (18,19,21,22).…”
Section: A B Cmentioning
confidence: 98%
“…The sample range was 29 to 973, with a median of 144. A total of 2118 surgical dissections were reported on nerve identification (15)(16)(17)(18)(19)(20)(21)(22). The objectives of Lange 2009, Grossi 2015 and Mendes 2016 were centered on the intraoperative identification of the nerves only.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…In OIHR surgery, the subcostal nerve (T12), ilioinguinal nerve (L1), iliohypogastric nerve (T12-L1), and sometimes the genitofemoral nerve (L1-L2) provide sensory innervation to the incision area [ 9 – 11 ]. According to the literature, II-IH and transversus abdominis plane (TAP) blocks are used most frequently to treat postoperative pain following OIHR surgery [ 12 ].…”
Section: Introductionmentioning
confidence: 99%